Additional Criminal Function in the Strategy for Combating Corruption Crimes - Karlina Apriani; Amiruddin Amiruddin; Rina Khairani Pancaningrum (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze additional criminal function in the strategy for combating corruption crimes. This type of research is normative law. The approach method used in this research are legislative, conceptual, and case. This research is normative legal research. Analysis of legal materials is carried out using the method of legal interpretation. The results show that additional criminal function that can be imposed on perpetrators of criminal acts of corruption as stipulated in article 18 of the anti-corruption law consist of additional criminal function confiscation or return of assets for criminal acts of corruption, additional criminal function of substitution, additional criminal function closure of whole or part of the company, and additional criminal function revocation of certain rights perpetrators of corruption crimes.